1999
DOI: 10.1038/45816
|View full text |Cite
|
Sign up to set email alerts
|

A kinase-regulated PDZ-domain interaction controls endocytic sorting of the β2-adrenergic receptor

Abstract: A fundamental question in cell biology is how membrane proteins are sorted in the endocytic pathway. The sorting of internalized beta2-adrenergic receptors between recycling endosomes and lysosomes is responsible for opposite effects on signal transduction and is regulated by physiological stimuli. Here we describe a mechanism that controls this sorting operation, which is mediated by a family of conserved protein-interaction modules called PDZ domains. The phosphoprotein EBP50 (for ezrinradixin-moesin(ERM)-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
651
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(705 citation statements)
references
References 26 publications
44
651
2
Order By: Relevance
“…Recent results have suggested a role for myosins in recycling (Neuhaus and Soldati, 2000;Lapierre et al, 2001), implying a role for the actin cytoskeleton in this process. Studies using drugs that depolymerize actin filaments also implicate actin at a recycling step (Durrbach et al, 1996;Cao et al, 1999;Zaslaver et al, 2001;Sheff et al, 2002;Engqvist-Goldstein and Drubin, 2003). We have found that an endosome-associated protein, hrs, is part of a protein complex that includes actinin-4, BERP, and myosin Vb, designated CART.…”
Section: Discussionmentioning
confidence: 97%
“…Recent results have suggested a role for myosins in recycling (Neuhaus and Soldati, 2000;Lapierre et al, 2001), implying a role for the actin cytoskeleton in this process. Studies using drugs that depolymerize actin filaments also implicate actin at a recycling step (Durrbach et al, 1996;Cao et al, 1999;Zaslaver et al, 2001;Sheff et al, 2002;Engqvist-Goldstein and Drubin, 2003). We have found that an endosome-associated protein, hrs, is part of a protein complex that includes actinin-4, BERP, and myosin Vb, designated CART.…”
Section: Discussionmentioning
confidence: 97%
“…A mutation in the distal portion of the b2-adrenergic receptor has been shown to disrupt a PDZ domainmediated interaction, resulting in reduced receptor recycling and increased targeting to lysosomes. 28 The clear association with female subjects affected with major mental illness and not with male subjects is intriguing. There is no reported gender bias in the numbers of individuals affected by BPAD.…”
Section: Discussionmentioning
confidence: 99%
“…PDZ domains are widespread among signaling and cytoskeletal proteins and are thought to function as molecular scaffolds for the assembly of multiprotein complexes and to localize them to specialized membrane and subcellular compartments (50). Thus, PDZ proteins are pivotal for the correct organization of protein complexes in cell-cell junctions (51), in phototransduction cascades (52), in neuronal synapses (53), and for sorting/targeting proteins to specific subcellular sites (54,55). PDZ domains generally recognize short sequence motifs present at the last four to five C-terminal residues on their target proteins and are typically grouped into three different classes: class I PDZ domains recognize the motif -X-(S/T)-X-, class II PDZ domains the motif -X--X-, and class III PDZ domains the motif D/E-X-( represents a bulky hydrophobic amino acid, and X any amino acid) (49).…”
Section: Discussionmentioning
confidence: 99%